Teaching Vocabulary Through Spelling Bee For Junior High School Students - Chairunisa, Auditha (Proceeding of International Conference on Language Pedagogy (ICOLP), 2023)
This research explains about Teaching Vocabulary Through Spelling Bee For Junior High School Students. Spelling bee as media learning english in the use of vocabulary. The purpose of this reseacrh is To know the student respon of the spelling bee to learn english vocabulary. Junior high school is the level of basic education in formal education in Indonesia which is taken after graduating from elementary school. This study uses quantitative as student data collection as the use of vocabulary in spelling bee. The participants of this study were 32 children from Junior High School. Based on the results of the student response questionnaire analysis, it is known that the advantages of teaching vocabulary in spelling bee for junior high schools are more prominent by 100% of the 32 students who think that the use of vocabulary through spelling bees, while the lack of teaching vocabulary in spelling bee for junior high school students in the questionnaire response is 3.1% or 1 student of 32 students. The data of this study were taken from grades 7-9 of junior high school students. This spelling bee is very useful so that students know their vocabulary mastery skills so that students must teach vocabulary through learning English for junior high school students.